The prevalence of hearing loss and use of hearing aids among adults in Germany: a systematic review - Löhler, Jan; Walther, Leif Erik (European archives of oto-rhino-laryngology and head & neck, 2019)
BackgroundWorldwide approximately 360 million people suffer from hearing impairment, 328 million of whom are adults. Up to now there has been no systematic evaluation of any representative epidemiological data on the prevalence of hearing loss among adults in Germany. The present paper is intended to investigate this within the framework of a systematic review.MethodsA systematic literature search was carried out in electronic databases as well as by means of hand-searching. Studies published after 1975 and indicating the prevalence or incidence of hearing impairment among German adults were included. Study selection, data extraction and additional quality assessments were made by two independent reviewers.ResultsBy means of a systematic literature search it was possible to identify 6 sources, which provided solely cross-sectional data, whereby the reported data are based on a study population of between some hundred and 10 million people living in Germany. The prevalences ascertained showed a broad range of between 16% and 25% and varied according to age, study setting, definition of hearing loss and method of data capture. At present there are no utilizable data on the extent of the use of hearing aids.DiscussionThe present review demonstrates clearly that evidence-based information relating to Germany can only be made on the basis of a clear definition of hearing loss within the framework of an up-to-date and representative epidemiological study carried out with appropriate methodology. In view of the high prevalence of illnesses causing hearing impairment and of the risks to health associated with untreated hearing impairment as well as of socio-economic costs, such an epidemiological study is of great social significance.